mRNA-103 inhibition attenuates autophagy and inflammation in myocardial infarction by regulating the TLR4 pathway - Fan Li; XiaoHui Ma; Tong Liu; Yang Wang; Xin Xie; Yi Xin; Kang Cheng (Archives of Medical Science)
Introduction This investigation determined the cardioprotective activity of mRNA-103 inhibitor against myocardial infarction (MI) and also evaluated its molecular mechanism.